Transformasi Digital Pengasapan Ikan: Pendampingan Implementasi IoT untuk Monitoring Suhu dan Meningkatkan Kualitas - Lutfi Syafirullah; Fajar Mahardika; Adlan Nugroho; Joko Purwanto; Kukuh Muhammad; Laura Sari; Ratih Hafsarah Maharrani (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2026)
Digital transformation in the traditional food processing sector has become a strategic step to enhance efficiency and product quality. This study aims to design and assist in the implementation of an Internet of Things (IoT) system for fish smoking equipment, particularly focusing on real-time temperature monitoring. By utilizing temperature sensors, microcontrollers, and cloud-based IoT platforms, the system enables business actors to supervise the smoking process accurately and continuously. Assistance was provided to local fish-smoking groups to ensure that the implemented technology can be operated independently and tailored to field needs. The implementation results showed an improvement in temperature consistency during the production process, which directly impacts the final product quality, especially in terms of taste, color, and shelf life of smoked fish. This study demonstrates that the integration of digital technology into traditional processing can increase product added value and strengthen the adaptive capacity of business actors in the Industry 4.0 era. The developed system also opens opportunities for replication in other agro-industrial sectors as part of strengthening a technology-based appropriate economy